Publisher Correction: Computational repositioning and preclinical validation of mifepristone for human vestibular schwannoma. Issue 1 (December 2018) - Sagers, Jessica; Brown, Adam; Vasilijic, Sasa; Lewis, Rebecca; Sahin, Mehmet; Landegger, Lukas; Perlis, Roy; Kohane, Isaac; Welling, D.; Patel, Chirag; Stankovic, Konstantina
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has been fixed in the paper.